IFN-α promotes rapid human Treg contraction and late Th1-like Treg decrease. Issue 3 (26th February 2016) - Pacella, Ilenia; Timperi, Eleonora; Accapezzato, Daniele; Martire, Carmela; Labbadia, Giancarlo; Cavallari, Eugenio N; D'Ettorre, Gabriella; Calvo, Ludovica; Rizzo, Fabiana; Severa, Martina; Coccia, Eliana M; Vullo, Vincenzo; et al.
Abstract : IFN-α restrains Tregs in vitro and in vivo via induced apoptosis, a decrease in Th1-like Tregs, inhibiting IL-12-driven polarization, and depleting IL-12 sources. Abstract: Type I IFNs are pleiotropic cytokines that exert concerted activities in the development of antiviral responses. Regulatory T cells represent a physiologic checkpoint in the balance between immunity and tolerance, requiring fine and rapid controls. Here, we show that human regulatory T cells are particularly sensitive to the sequential effects of IFN-α. First, IFN-α exerts a rapid, antiproliferative and proapoptotic effect in vitro and in vivo, as early as after 2 d of pegylated IFN/ribavirin therapy in patients with chronic hepatitis C. Such activities result in the decline, at d 2, in circulating regulatory T cell frequency and specifically of the activated regulatory T cell subset. Later, IFN-based therapy restrains the fraction of regulatory T cells that can be polarized into IFN-γ-producing Th1-like regulatory T cells known to contribute to chronic immune activation in type 1 inflammation. Indeed, Th1-like regulatory T cell frequency significantly declines after 30 d of therapy in vivo in relation to the persistent decline of relevant IL-12 sources, namely, myeloid and 6-sulfo LacNAc-expressing dendritic cells. This event is recapitulated by experiments in vitro, providing evidence that it may be attributable to the inhibitory effect of IFN-α on IL-12-induced, Th1-like regulatory T cell polarization. In summary, our results suggest that IFN-α-driven, early regulatory T cell depletion contributes to the development of antiviral immunity, ultimately resulting in the resolution of type 1 inflammation.